2006
DOI: 10.1677/joe.1.07016
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor regulates insulin-like growth factor-I receptor gene expression in breast tumor cells: involvement of transcription factor Sp1

Abstract: The insulin-like growth factors, IGF-I and IGF-II are a family of mitogenic polypeptides with important roles in growth and differentiation. The biological actions of the IGFs are mediated by the IGF-I receptor (IGF-IR), a cell-surface tyrosine kinase, whose activation by serum IGF-I seems to be a key step in breast cancer initiation. Evidence accumulated indicates that estrogens stimulate the expression and activity of IGF axis components. The aim of our study was to examine the transcriptional mechanisms inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(80 citation statements)
references
References 47 publications
4
76
0
Order By: Relevance
“…Thus, the latter dose was used in further experiments. Incidentally, it should be noted that concentrations in the high-nM range have been largely used to investigate gene transcriptional regulation by E 2 [23][24][25][26][27] or metabolic effect of this hormone [28]. Moreover, it has been shown that intratesticular concentrations are much higher than serum levels of E 2 [29].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the latter dose was used in further experiments. Incidentally, it should be noted that concentrations in the high-nM range have been largely used to investigate gene transcriptional regulation by E 2 [23][24][25][26][27] or metabolic effect of this hormone [28]. Moreover, it has been shown that intratesticular concentrations are much higher than serum levels of E 2 [29].…”
Section: Resultsmentioning
confidence: 99%
“…SP1 has been described as an activator of many genes (Suske 1999). With respect to insulin/IGF1R signaling it has been shown that SP1 is also involved in the regulation of the insulin receptor gene itself (Foti et al 2003) as well as the IGF1R gene (Maor et al 2006). Since there are multiple potential binding sites for SP1 in the IRS2 promoter, Vassen et al (1999), the authors of the first description of the human IRS2 promoter sequence speculated about a major role for SP1 in the transcriptional regulation of the IRS2 gene (Vassen et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…ChIP Assays-ChIP assays were performed as described previously (22,30). Briefly, MCF7 and C4.12.5 cells were crosslinked with 1% formaldehyde at 37°C for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…The IGFs and estrogen act in a synergistic fashion in breast epithelial cells (27), and both the MAPK and Akt pathways were shown to mediate the activation of ER␣ by IGF-I (28,29). On the other hand, estrogens regulate IGF-I signaling and the expression of key members of the IGF axis (30). Furthermore, estrogens were shown to induce a physical interaction between ER␣ and IGF-IR, leading to activation and phosphorylation of IGF-IR and downstream signaling molecules (31).…”
mentioning
confidence: 99%